Real time control of an active power filter under distorted voltage condition - Ahmed Safa; Gouichiche Madjid; Meslem Youcef; Tedjini Hamza (Institute of Advanced Engineering and Science, 2012)
This paper, presents three phase shunt active filter under distorted voltage condition, the active power filter control is based on the use of self-tuning filter (STF) for reference current generation and on space vector PWM for generation of pulses. The dc capacitor voltage is controlled by a classical PI controller. The diode rectifier feed RL load is taken as a nonlinear load. The self-tuning filter allows extracting directly the voltage and current fundamental components in the axis without phase locked loop (PLL) under distorted voltage condition. The experiment analysis is made based on working under distorted voltage condition, and the total harmonic distortion of source current after compensation .Self tuning filter based extraction technique is good under distorted voltage conditions. The total harmonic distortion (THD) of source current is fully reduced. The effectiveness of the method is theoretically studied and verified by experimentation.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.397